Hole transport layer, preparation method thereof and perovskite solar cell thereof

By using a hybrid self -assembly single molecular material and the precursor of the perovskite before the annealing process is used to form an empty acupoint transmission layer during the annealing process, it solves the efficiency and stability in long -term use of perovskite solar cells. Poor problems have achieved efficient and stable photoelectric performance.

CN119365044APending Publication Date: 2025-01-24TRINA SOLAR CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411403768.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing perovskite solar cells have poor efficiency and stability under the long-term effects of water, oxygen, light and heat, and the hole transport layer in trans perovskite solar cells have poor wetting properties, which affects the photoelectric performance and preparation process of the battery. .

Method used

The hybrid self -assembly single molecular material and the perovskite prefrontal solution were used to assemble the acupoint transmission layer by self -assembly during the annealing process to simplify the crystallization growth of the oscopic film and the photoelectric performance of the battery.

Benefits of technology

Through this method, the photovoltaic performance of the perovskite solar cell has been significantly improved, the opening voltage loss is reduced, and it is suitable for the preparation of large -scale perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365044A_ABST
    Figure CN119365044A_ABST
Patent Text Reader

Abstract

The invention provides a method for allocating the performance of a hole transport layer and a perovskite solar cell thereof, and particularly provides a method for preparing the hole transport layer, and the method comprises the steps: applying a solution to a substrate, and carrying out the annealing treatment, so as to form the hole transport layer; wherein the solution comprises a perovskite precursor and at least two self-assembly monomolecular materials. A mixed self-assembled monomolecular material body phase is doped with a perovskite precursor solution, and in the annealing process, the self-assembled monomolecular material can be automatically buried at an interface at the bottom of a perovskite thin film to form a hole transport layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to a hole transport layer, a method for preparing the hole transport layer, and a perovskite solar cell thereof. Background Art

[0002] As a clean and renewable energy source, solar energy has received extensive attention from academia and industry. At present, perovskite solar cells (PSCs) have attracted much attention among the third generation of solar cells due to their excellent optoelectronic performance, high photoelectric conversion efficiency (the highest certified efficiency of single-junction perovskite solar cells has reached 26.1%), low solution preparation cost and simple process. At present, the structure of formal and trans perovskite solar cells is mainly composed of an electron transport layer (ETL), a perovskite light absorption layer, a hole transport layer (HTL) and a metal electrode. However, the efficiency and stability of the perovskite light absorption layer are poor under the long-term effects of water, oxygen, light and heat, which also leads to a decrease in the service life of perovskite solar cells, seriously affecting the commercial application of the battery. In addition, for trans perovskite solar cells, the presence of HTL also has many effects on the performance and preparation process of the battery, such as poor energy level matching leading to the loss of open circuit voltage, poor wettability affecting the large-area preparation and nucleation growth of perovskite films, etc. These problems will directly affect the final optoelectronic performance of perovskite solar cells. In inverted perovskite solar cells, the hole transport layer serves as the substrate of the perovskite light absorption layer to extract holes and transfer them to the electrode. Existing technologies mainly improve the wettability of the perovskite substrate and adjust the energy level of the perovskite solar cell by optimizing the performance of the HTL material or adding surfactants, and combine the perovskite passivation strategy to reduce the defects of the perovskite bulk phase and surface interface, further reduce the non-radiative recombination of carriers in the perovskite cell, and improve the photoelectric performance and stability of the cell.

[0003] However, the various preparation methods and strategies mentioned above still have many problems, such as the need for simpler preparation processes, more effective passivators, and simpler passivation methods to achieve high-efficiency and long-term stable perovskite solar cells. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems existing in the prior art to at least a certain extent.

[0005] Therefore, in the first aspect of the present application, the present application proposes a method for preparing a hole transport layer. According to an embodiment of the present application, the method comprises: applying a solution on a substrate for annealing to form a hole transport layer; wherein the solution comprises a perovskite precursor and at least two self-assembled monomolecular materials.

[0006] By using a mixed self-assembled monomolecular material bulk phase doped perovskite precursor solution, during the annealing process, the self-assembled monomolecular material is automatically buried at the interface at the bottom of the perovskite film and forms a hole transport layer. The method described in this application not only simplifies the preparation process of perovskite solar cells, but also solves the problem of poor wettability of the hole transport layer during the preparation of perovskite solar cells, can effectively improve the photoelectric performance of the battery, and is suitable for preparing large-area perovskite solar cells.

[0007] According to an embodiment of the present application, the above method for preparing a hole transport layer may further include at least one of the following additional technical features:

[0008] According to an embodiment of the present application, there are two types of self-assembled monomolecular materials, and the mass ratio of the two types of self-assembled monomolecular layer materials is 1:1 to 1:10.

[0009] According to an embodiment of the present application, the self-assembled monomolecular material includes at least one of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACZ), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACZ), [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-4PACZ), (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanotitanyl)phosphonic acid (MPA-CPA) and [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid (DMAcPA).

[0010] According to an embodiment of the present application, the two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid.

[0011] According to an embodiment of the present application, the two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid.

[0012] According to an embodiment of the present application, the two self-assembled monomolecular materials include [2-(9H-carbazol-9-yl)ethyl]phosphonic acid and [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid.

[0013] According to an embodiment of the present application, the two self-assembled monomolecular materials include [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid.

[0014] According to an embodiment of the present application, the mass ratio of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid is (1-3):1.

[0015] According to an embodiment of the present application, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to the [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid is (0.5-1.5):1.

[0016] According to an embodiment of the present application, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to the [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid is 1:(1-3).

[0017] According to an embodiment of the present application, the mass ratio of [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid is (1-3):1.

[0018] According to an embodiment of the present application, the concentrations of the at least two self-assembled monomolecular materials in the solution are respectively 0.5 mg / mL to 20 mg / mL.

[0019] According to an embodiment of the present application, the concentrations of the at least two self-assembled monomolecular materials in the solution are respectively 1 mg / mL to 10 mg / mL.

[0020] According to an embodiment of the present application, the annealing process includes one-step annealing or two-step annealing.

[0021] According to an embodiment of the present application, the one-step annealing is performed at 60-180° C. for 1-80 min.

[0022] According to an embodiment of the present application, the two-step annealing includes firstly performing annealing at 50-100° C. for 1-30 min; and then performing annealing at 80-180° C. for 1-60 min.

[0023] According to an embodiment of the present application, the perovskite precursor is provided in the form of a perovskite precursor solution.

[0024] According to an embodiment of the present application, the perovskite precursor solution is prepared in the following manner: a metal halide, an organic salt halide and an organic solvent are mixed to obtain a perovskite precursor solution.

[0025] According to an embodiment of the present application, the metal halide includes at least two selected from rubidium iodide (RbI), cesium chloride (CsCl), rubidium chloride (RbCl), cesium iodide (CsI), cesium chloride (CsCl), lead iodide (PBI) and lead chloride (PBCl).

[0026] According to an embodiment of the present application, the organic salt halide includes at least two selected from formamidine iodine (FAI), formamidine bromide (FABr), formamidine chloride (FACl), methylamine iodine (MAI), methylamine bromide (MABr) and methylamine chloride (MACl).

[0027] According to an embodiment of the present application, the organic solvent includes at least one selected from dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), acetonitrile (ACN), dimethylpyrrolidone (NMP), 2-methoxyethanol and γ-butyrolactone.

[0028] In the second aspect of the present application, the present application proposes a hole transport layer. According to an embodiment of the present application, the hole transport layer is prepared by the method described in the first aspect. The hole transport layer prepared by the method described in the present application is conducive to improving the crystal growth of perovskite film and the photoelectric performance of the battery, is suitable for the preparation of large-area perovskite solar cells, and has wide applicability for defect passivation and energy level adjustment in the preparation process of large-area perovskite solar cells.

[0029] In the third aspect of the present application, the present application proposes a hole transport layer. According to an embodiment of the present application, the hole transport layer comprises: composed of at least two self-assembled monomolecular materials; wherein the self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACZ), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACZ), [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-4PACZ), (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanotitanyl)phosphonic acid (MPA-CPA) or [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid (DMAcPA).

[0030] By mixing self-assembled monolayer materials with different band gaps, not only can the defects in the perovskite film be synergistically passivated, the defect density of the perovskite light absorption layer can be reduced, and the non-radiative recombination of the perovskite film can be reduced, but also excellent energy level matching with the perovskite light absorption layer can be achieved to reduce the open circuit voltage loss, which is more conducive to the transmission and extraction of holes. In order to meet the different perovskite energy level matching requirements, this application selects two self-assembled monolayer materials, and by optimizing the ratio between the two, a hole transport layer with the best work function is obtained.

[0031] In the fourth aspect of the present application, the present application proposes a perovskite solar cell. According to an embodiment of the present application, the perovskite solar cell includes: a substrate; a hole transport layer, the hole transport layer is as defined in the second aspect and the third aspect, and the hole transport layer is arranged on one side of the substrate; a perovskite absorption layer, the perovskite absorption layer is arranged on the side of the hole transport layer away from the substrate; an electron transport layer, the electron transport layer is arranged on the side of the perovskite absorption layer away from the hole transport layer; an electrode layer, the electrode layer is arranged on the side of the electron transport layer away from the perovskite absorption layer. As mentioned above, the hole transport layer preparation method mentioned in the present application successfully avoids the problem of poor wettability of the hole transport layer in the previous battery preparation process. In addition, it can effectively reduce the open circuit voltage loss and significantly improve the transmission and extraction efficiency of holes. Therefore, the battery designed in the present application exhibits excellent photoelectric performance, and the voltage, current, fill factor and efficiency are all improved.

[0032] According to an embodiment of the present application, the above-mentioned perovskite solar cell may further include the following additional technical features:

[0033] According to an embodiment of the present application, the perovskite solar cell further includes: a buffer layer, wherein the buffer layer is disposed between the electron transport layer and the electrode layer.

[0034] According to an embodiment of the present application, the perovskite solar cell further includes: a passivation layer, wherein the passivation layer is disposed between the perovskite absorption layer and the electron transport layer.

[0035] In the fifth aspect of the present application, the present application proposes a perovskite tandem cell. According to an embodiment of the present application, the perovskite tandem cell comprises: a top cell and a bottom cell, the top cell is the perovskite solar cell described in the fourth aspect, and the top cell is arranged on the upper surface of the bottom cell. Therefore, the advantages of the perovskite solar cell of the present application can also be reflected in the perovskite tandem cell, including excellent photoelectric performance.

[0036] In the sixth aspect of the present application, the present application proposes an electrical device. According to an embodiment of the present application, the electrical device includes: the perovskite solar cell described in the fourth aspect or the perovskite tandem cell described in the fifth aspect.

[0037] Beneficial effects:

[0038] (1) By directly dissolving a variety of self-assembled monomolecular materials into a perovskite precursor solution for device preparation, the process steps of preparing a hole transport layer separately are reduced, thus shortening the device preparation cycle;

[0039] (2) Various groups in the self-assembled monomolecular material can effectively passivate the defects of the perovskite film, reduce the defect density of the perovskite light absorption layer, and reduce the non-radiative recombination of the perovskite film, thereby improving the efficiency and stability of the device;

[0040] (3) The present application does not need to prepare a hole transport layer on the conductive glass, thus successfully avoiding the disadvantage of poor wettability of the hole transport layer in the traditional inverse perovskite solar cell. This improvement helps to improve the film growth of the perovskite film and is particularly suitable for the preparation process of large-area perovskite solar cells.

[0041] (4) By adjusting the proportion or type of a variety of self-assembled single-molecule materials, the band gap of the perovskite solar cell can be effectively adjusted, thereby optimizing the energy band structure of the battery, making it more compatible with the energy band of the perovskite light-absorbing layer, and more conducive to the transmission and extraction of holes.

[0042] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0044] Figure 1 is a schematic diagram of a hole transport layer and a perovskite film according to an embodiment of the present application;

[0045] Figure 2 is a schematic structural diagram of a titanium ore solar cell according to an embodiment of the present application;

[0046] Figure 3 is a schematic diagram of the structure of a titanite solar cell containing a buffer layer according to an embodiment of the present application;

[0047] Figure 4 is a schematic structural diagram of a titanium ore solar cell with a passivation layer according to an embodiment of the present application;

[0048] Figure 5 is a schematic diagram of the structure of a titanite solar cell including a buffer layer and a passivation layer according to an embodiment of the present application;

[0049] Figure numerals: 01: substrate; 02: hole transport layer; 03: perovskite film; 001: substrate; 002: hole transport layer; 003: perovskite absorption layer; 004: electron transport layer; 005: electrode layer; 006: buffer layer; 007: passivation layer. DETAILED DESCRIPTION

[0050] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0051] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0052] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0054] In this document, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0055] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0056] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0057] Method for preparing hole transport layer

[0058] In one aspect of the present application, the present application proposes a method for preparing a hole transport layer. According to an embodiment of the present application, the method comprises: applying a solution on a substrate for annealing to form a hole transport layer; wherein the solution comprises a perovskite precursor and at least two self-assembled monomolecular materials.

[0059] By using a mixed self-assembled monomolecular material bulk phase doped perovskite precursor solution, during the annealing process, the self-assembled monomolecular material is automatically buried at the interface at the bottom of the perovskite film and forms a hole transport layer. The method described in this application not only reduces the preparation steps of the hole transport layer and shortens the preparation cycle of the device, but also solves the problem of poor wettability of the hole transport layer during the preparation of perovskite solar cells, thereby improving the crystal growth of the perovskite film, and therefore, can effectively improve the photoelectric performance of the battery, and is suitable for preparing large-area perovskite solar cells.

[0060] Specifically, Figure 1 As shown, during the annealing treatment, the perovskite precursor will form a perovskite film 03 on the upper surface of the substrate 01, and the self-assembled monomolecular material will spontaneously diffuse downward to the lower interface of the perovskite film to form a hole transport layer 02 (the perovskite film and the hole transport layer are formed at the same time). In addition, the self-assembled monomolecular material in the perovskite can also synergistically passivate the defects in the bulk and surface interface of the perovskite film, reduce the defect density of the perovskite light absorption layer, and reduce the non-radiative recombination of the perovskite film.

[0061] The specific type of the above-mentioned substrate is not particularly limited, and a commonly used conductive glass substrate or a velvet substrate can be used. The conductive glass can be, for example, ITO (indium tin oxide) transparent conductive glass, FTO (fluorine-doped tin oxide) transparent conductive glass, IWO (tungsten-doped indium oxide) transparent conductive glass, and AZO (aluminum-doped zinc oxide) transparent conductive glass, etc. The velvet substrate can be, for example, a crystalline silicon velvet substrate of a perovskite-silicon stacked solar cell and other velvet substrates.

[0062] In some embodiments of the present application, there are two types of self-assembled monolayer materials, and the mass ratio of the two types of self-assembled monolayer materials is 1:1 to 1:10. In a specific embodiment, two types of self-assembled monolayer materials can be selected for mixing according to different perovskite energy level matching requirements, and by optimizing the ratio between the two components, the band gap of the perovskite solar cell can be adjusted, thereby optimizing the energy band structure of the battery, making it more matched with the energy band of the perovskite light absorption layer, and more conducive to the transmission and extraction of holes.

[0063] In some embodiments of the present application, the mass ratio of the two self-assembled monolayer materials can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc., or can be a range consisting of any of the above numerical values.

[0064] In some embodiments of the present application, the self-assembled monomolecular material includes at least one of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACZ), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACZ), [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-4PACZ), (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanotitanyl)phosphonic acid (MPA-CPA) and [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid (DMAcPA). By adjusting the type of mixed self-assembled monomolecular materials, the band gap of the perovskite solar cell can be adjusted to make it more matched with the energy band of the perovskite light absorption layer, which is beneficial to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0065] It should be noted that the "self-assembled monomolecular material" may refer to one of the above-mentioned materials or to a plurality of the above-mentioned materials, that is, the "self-assembled monomolecular material" may refer to 2PACZ alone or to a combination of 2PACZ and MeO-2PACZ. In this case, the aforementioned "at least two self-assembled monomolecular materials" may refer to at least two separate self-assembled monomolecular materials or to a combination of at least two self-assembled monomolecular materials.

[0066] In some embodiments of the present application, the two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid. Therefore, it can better match the energy band of the perovskite light absorption layer, which is beneficial to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0067] In some embodiments of the present application, the mass ratio of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid is (1-3):1. As an example, the mass ratio of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid can be 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1, etc., or can be a range composed of any of the above values. Therefore, it can better match the energy band of the perovskite light absorption layer, which is more conducive to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0068] In some embodiments of the present application, the two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid. Therefore, it can better match the energy band of the perovskite light absorption layer, which is beneficial to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0069] In some embodiments of the present application, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to the [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid is (0.5-1.5):1. As an example, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to the [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid may be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc., or may be a range of any of the above values. Therefore, it can better match the energy band of the perovskite light absorption layer, which is more conducive to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0070] In some embodiments of the present application, the two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid. Therefore, it can better match the energy band of the perovskite light absorption layer, which is beneficial to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0071] In some embodiments of the present application, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and the [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid is 1:(1-3). As an example, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and the [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid is 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1, etc., or can be a range composed of any of the above values. Therefore, it can better match the energy band of the perovskite light absorption layer, which is more conducive to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0072] In some embodiments of the present application, the two self-assembled monomolecular materials include [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid. Therefore, it can better match the energy band of the perovskite light absorption layer, which is beneficial to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0073] In some embodiments of the present application, the mass ratio of [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid is (1-3):1. As an example, the mass ratio of [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid is 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1, etc., or can be a range composed of any of the above values. Therefore, it can better match the energy band of the perovskite light absorption layer, which is more conducive to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0074] In some embodiments of the present application, the concentration of the at least two self-assembled monomolecular materials in the solution is 0.5 mg / mL to 20 mg / mL, for example, 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 8 mg / mL, 10 mg / mL, 12 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 18 mg / mL, 20 mg / mL, etc., or it can be a range composed of any of the above values. Therefore, when the concentration of the self-assembled monomolecular material is within the above range, the hole transport layer can be better formed, so that it can better match the energy band of the perovskite light absorption layer, which is more conducive to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0075] In some embodiments of the present application, the concentrations of the at least two self-assembled monomolecular materials in the solution are 1 mg / mL to 10 mg / mL, respectively.

[0076] In some embodiments of the present application, the annealing treatment includes one-step annealing or two-step annealing. Through the annealing treatment, the growth of perovskite crystals can be promoted, defects and impurities inside the crystals can be reduced, the crystal quality and photoelectric properties of the film can be improved, and the quality and performance of the perovskite film can be improved.

[0077] In some embodiments of the present application, the one-step annealing is performed at 60-180° C. for 1-80 min. Therefore, the growth of perovskite crystals can be promoted.

[0078] As an example, the temperature of the one-step annealing can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc., or can be a range consisting of any of the above numerical values.

[0079] As an example, the one-step annealing time may be 1 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, etc., or may be a range consisting of any of the above values.

[0080] In some embodiments of the present application, the two-step annealing includes firstly performing annealing at 50-100° C. for 1-30 min; and then performing annealing at 80-180° C. for 1-60 min.

[0081] As an example, the temperature of the first step of the two-step annealing may be 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., etc., or may be a range consisting of any of the above values.

[0082] As an example, the first step of the two-step annealing can be 1 min, 5 min, 8 min, 10 min, 13 min, 15 min, 18 min, 20 min, 23 min, 25 min, 28 min, 30 min, etc., or can be a range consisting of any of the above values.

[0083] As an example, the second step temperature of the two-step annealing can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc., or can be a range consisting of any of the above numerical values.

[0084] As an example, the second step time of the two-step annealing can be 1 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc., or can be a range consisting of any of the above numerical values.

[0085] In some embodiments of the present application, the perovskite precursor is provided in the form of a perovskite precursor solution. The perovskite precursor solution can be used to prepare a perovskite absorption layer, and the perovskite absorption layer includes an ABX3 type perovskite, wherein A is one or more of methylamine, formamidine, acetamidine, cesium or rubidium; B is one or more of lead, tin, copper and germanium; X is F - ,I - Br - , Cl - 、BF4 - PF6 - and SCN - One or more of the .

[0086] In some embodiments of the present application, the perovskite precursor solution is prepared by mixing a metal halide, an organic salt halide and an organic solvent to obtain a perovskite precursor solution. By adopting this method, a high-quality perovskite film having ABX3-type perovskite can be prepared.

[0087] In some embodiments of the present application, the metal halide includes at least two selected from rubidium iodide (RbI), cesium chloride (CsCl), rubidium chloride (RbCl), cesium iodide (CsI), cesium chloride (CsCl), lead iodide (PbI) and lead chloride (PbCl).

[0088] In some embodiments of the present application, the concentration of divalent metal ions in the perovskite precursor solution is 200 mg / mL to 600 mg / mL.

[0089] In some embodiments of the present application, the organic salt halide includes at least two selected from formamidine iodine (FAI), formamidine bromide (FABr), formamidine chloride (FACl), methylamine iodine (MAI), methylamine bromide (MABr) and methylamine chloride (MACl).

[0090] In some embodiments of the present application, the organic solvent includes at least one selected from dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), acetonitrile (ACN), dimethylpyrrolidone (NMP), 2-methoxyethanol and γ-butyrolactone.

[0091] It should be noted that the perovskite film preparation process corresponding to different organic solvent systems is different. When using DMF+DMSO solvent, the anti-solvent method is generally used, that is, non-polar solvents such as chlorobenzene, ether or anisole (i.e., anti-solvent) are added dropwise during the spin coating of the perovskite solution to quickly extract solvents such as DMF / DMSO, so as to promote the crystallization of perovskite to form a uniform and dense film. When using solvent systems such as DMF+NMP, DMF+CAN or CAN, the anti-solvent-free method is generally used, that is, it is not necessary to add anti-solvents during the preparation of the perovskite film. According to the embodiments of the present application, whether the anti-solvent method or the anti-solvent-free method is used to prepare the perovskite film, a variety of self-assembled monomolecular materials are added to the perovskite precursor solution, and the self-assembled monomolecular materials can be realized to form a hole transport layer from the bottom during the annealing process.

[0092] Hole transport layer

[0093] The present application proposes a hole transport layer. According to an embodiment of the present application, the hole transport layer is prepared by the method described in the first aspect. The hole transport layer prepared by the method described in the present application is conducive to improving the crystal growth of perovskite film and the photoelectric performance of the battery, is suitable for the preparation of large-area perovskite solar cells, and has wide applicability to defect passivation and energy level adjustment in the preparation process of large-area perovskite solar cells.

[0094] The present application proposes a hole transport layer. According to an embodiment of the present application, the hole transport layer comprises: composed of at least two self-assembled monomolecular materials; wherein the self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACZ), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACZ), [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-4PACZ), (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanotitanyl)phosphonic acid (MPA-CPA) or [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid (DMAcPA).

[0095] It should be noted that when the at least two self-assembled monomolecular materials include [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid and [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid, the mass ratio of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid and [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid is not 2:1; when the at least two self-assembled monomolecular materials include [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, the mass ratio of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(9H-carbazole-9-yl)ethyl]phosphonic acid is not 1:1.

[0096] By mixing self-assembled monolayer materials with different band gaps, not only can the defects in the perovskite film be synergistically passivated, the defect density of the perovskite light absorption layer can be reduced, and the non-radiative recombination of the perovskite film can be reduced, but also excellent energy level matching with the perovskite light absorption layer can be achieved to reduce the open circuit voltage loss, which is more conducive to the transmission and extraction of holes. In order to meet the different perovskite energy level matching requirements, this application selects two self-assembled monolayer materials, and by optimizing the ratio between the two, a hole transport layer with the best work function is obtained.

[0097] In some embodiments of the present application, the two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid. Therefore, it can better match the energy band of the perovskite light absorption layer, which is beneficial to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0098] In some embodiments of the present application, the mass ratio of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid is (1.1-3): 1. Therefore, it can better match the energy band of the perovskite light absorption layer, which is more conducive to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0099] As an example, the mass ratio of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid can be 1.1:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1, etc., or can be a range consisting of any of the above numerical values.

[0100] In some embodiments of the present application, the two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid. Therefore, it can better match the energy band of the perovskite light absorption layer, which is beneficial to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0101] In some embodiments of the present application, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to the [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid is (0.5-1.5): 1. Therefore, it can better match the energy band of the perovskite light absorption layer, which is more conducive to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0102] As an example, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to the [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc., or can be a range consisting of any of the above numerical values.

[0103] In some embodiments of the present application, the two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid. Therefore, it can better match the energy band of the perovskite light absorption layer, which is beneficial to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0104] In some embodiments of the present application, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to the [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid is 1:(1-3). Therefore, it can better match the energy band of the perovskite light absorption layer, which is more conducive to the transmission and extraction of holes, thereby reducing the open circuit voltage loss of the battery.

[0105] As an example, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and the [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid is 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1, etc., or can be a range consisting of any of the above numerical values.

[0106] Perovskite solar cells

[0107] The present application proposes a perovskite solar cell. According to an embodiment of the present application, referring to Figure 2 , the perovskite solar cell comprises:

[0108] Base 001;

[0109] A hole transport layer 002, wherein the hole transport layer 002 is as defined in the second aspect and the third aspect, and the hole transport layer 002 is disposed on one side of the substrate 001;

[0110] A perovskite absorption layer 003, wherein the perovskite absorption layer 003 is disposed on a side of the hole transport layer 002 away from the substrate 001;

[0111] An electron transport layer 004, wherein the electron transport layer 004 is disposed on a side of the perovskite absorption layer 003 away from the hole transport layer 002;

[0112] The electrode layer 005 is arranged on a side of the electron transport layer 004 away from the perovskite absorption layer 003 .

[0113] As mentioned above, the hole transport layer mentioned in this application successfully solves the problem of poor wettability of the hole transport layer in the previous battery preparation process. In addition, it can effectively reduce the open circuit voltage loss and significantly improve the transmission and extraction efficiency of holes. Therefore, the battery designed in this application exhibits excellent photoelectric performance, and the voltage, current, fill factor and efficiency are all improved.

[0114] In some embodiments of the present application, reference Figure 3 or Figure 4 The perovskite solar cell further includes: a buffer layer 006 or a passivation layer 007 , the buffer layer 006 is arranged between the electron transport layer 004 and the electrode layer 005 , and the passivation layer 007 is arranged between the perovskite absorption layer 003 and the electron transport layer 004 .

[0115] In some embodiments of the present application, reference Figure 5 The perovskite solar cell further includes: a buffer layer 006 and a passivation layer 007 , the buffer layer 006 is arranged between the electron transport layer 004 and the electrode layer 005 , and the passivation layer 007 is arranged between the perovskite absorption layer 003 and the electron transport layer 004 .

[0116] Among them, a buffer layer is set between the electron transport layer and the electrode layer, which can make the energy levels on the electron transport path more matched, accelerate electron extraction and transmission, and reduce the interface recombination current; on the other hand, it can also protect the perovskite light absorption layer, thereby improving the stability of the battery; the passivation layer between the electron transport layer and the absorption layer mainly passesivates the defects of the perovskite film and reduces the non-radiative recombination of carriers in the perovskite film; it can also form an energy level gradient between the electron transport layers, promote the extraction and transmission of electrons, and thus improve the photoelectric performance of perovskite solar cells.

[0117] In some embodiments of the present application, the substrate may be a commonly used conductive glass substrate or a velvet substrate. The conductive glass may be, for example, ITO (indium tin oxide) transparent conductive glass, FTO (fluorine-doped tin oxide) transparent conductive glass, IWO (tungsten-doped indium oxide) transparent conductive glass, and AZO (aluminum-doped zinc oxide) transparent conductive glass, etc. The velvet substrate may be, for example, a crystalline silicon velvet substrate of a perovskite-silicon stacked solar cell and other velvet substrates.

[0118] In some embodiments of the present application, the components of the electron transport layer may be electron transport materials commonly used in the art, including but not limited to [6,6]-phenyl-C 61 -Methyl butyrate (PC 61 BM), [6,6]-phenyl-C 71 -Methyl butyrate (PC 71 BM), fullerene C 60 , Fullerene C 70 , at least one of tin dioxide and zinc oxide, can be formed by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating and the like. The preferred thickness of the electron transport layer is 10 to 40 nm.

[0119] In some embodiments of the present application, the electrode layer is a metal electrode or a transparent electrode. The metal electrode may be, for example, a silver electrode (Ag), a copper electrode (Cu), a gold electrode (Au), an aluminum electrode (Al), a molybdenum electrode (Mo), or a chromium electrode (Cr); the transparent electrode may be, for example, tin-doped indium oxide (ITO), indium zinc oxide (IZO), tungsten-doped indium oxide (IWO), aluminum-doped zinc oxide (AZO), fluorine-doped tin oxide (FTO), zinc oxide, etc. The electrode layer may be formed by evaporation, sputtering, chemical bath deposition, blade coating, slit coating, etc. The thickness of the electrode layer is 60 to 250 nm, preferably 100 to 200 nm.

[0120] In some embodiments of the present application, the material of the buffer layer includes one of BCP (2,9-dimethyl-4,7-biphenyl-1,10-phenanthroline), MoOx or tin dioxide (SnO2), and can be formed by evaporation, sputtering, chemical bath deposition, blade coating, slit coating and the like. The thickness of the buffer layer is 1 to 50 nm, preferably 10 to 30 nm.

[0121] In some embodiments of the present application, the material of the passivation layer includes alkaline halides, organic molecules, organic halide salts, polymers, metal halides, etc., preferably organic molecules and organic halide salts.

[0122] In some embodiments of the present application, the organic molecules include p-bromobenzonitrile (PBBN), 1,3-dimethyl-3-imidazole hexafluorophosphate (DMIMPF6), and the like.

[0123] In some embodiments of the present application, the organic halide salt includes methylamino bromide (MABr), phenethylammonium iodide (PEAI), tetrafluoro-phenethylammonium iodide (4F-PEAI), phenethylammonium bromide (PEABr), propylamine (PACl), and the like.

[0124] Perovskite tandem battery

[0125] The present application proposes a perovskite tandem cell. According to an embodiment of the present application, the perovskite tandem cell comprises: a top cell and a bottom cell, the top cell is the aforementioned perovskite solar cell, and the top cell is arranged on the upper surface of the bottom cell. Therefore, the perovskite tandem cell has all the advantages of a perovskite solar cell, which will not be described in detail here.

[0126] In some embodiments of the present application, the perovskite tandem cell can be selected from any one of a perovskite / crystalline silicon tandem cell, a full perovskite tandem cell, a perovskite / organic tandem cell, and a perovskite / CIGS tandem cell.

[0127] Electrical equipment

[0128] The present application proposes an electrical device. According to an embodiment of the present application, the electrical device includes the aforementioned perovskite solar cell or the aforementioned perovskite stacked cell. Therefore, the electrical device has all the advantages of the perovskite solar cell, which will not be described in detail here.

[0129] Specifically, electrical equipment may include lighting elements, display elements, mobile devices, etc., and may specifically include street lights, signal indicators, insect killer lamps, electric fans, electric toys, electric tools, battery vehicles, electric vehicles, ships, spacecraft, etc., among which electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft may include airplanes, rockets, space shuttles and spacecraft, etc.; photovoltaic power generation systems may include large-scale ground photovoltaic power generation systems, distributed photovoltaic power generation and building integrated photovoltaic power generation systems, etc.

[0130] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0131] Example 1

[0132] The preparation method of the perovskite solar cell 1 is as follows, wherein the perovskite film is prepared by an anti-solvent method:

[0133] 1. Mix FAI, PbI2, MACl, MAI, and CsI powders according to the molar ratio, add 1 mL of organic solvent (DMF:DMSO = 4:1) to dissolve, and obtain Cs 0.05 FA 0.90 MA 0.05 PbI3 perovskite precursor solution; then adding SAM material to the perovskite precursor solution, wherein the amount of 2PACZ added is twice that of MeO-2PACZ (mass ratio of 2PACZ:MeO-2PACZ=2:1), and the concentration of 2PACZ in the perovskite precursor solution is 4 mg / mL;

[0134] 2. Clean the ITO glass and blow dry it with nitrogen;

[0135] 3. The perovskite precursor solution with added SAM (self-assembled monomolecule) material is used to prepare a perovskite film on ITO as a light absorption layer by spin coating. During the process of adding anti-solvent and annealing, the mixed SAM material in the perovskite precursor solution diffuses downward along the grain boundary of the perovskite, automatically assembles / buries at the bottom of the perovskite film to form a hole transport layer. At the same time, the SAM remaining in the bulk and surface interface of the perovskite film can effectively passivate the defects of the perovskite film.

[0136] 4. On the perovskite film prepared in step 3 above, 30 nm thick C 60, 6nm thick BCP and 150nm thick Au electrode.

[0137] Example 2

[0138] The preparation method of the perovskite solar cell 2 is as follows, wherein the perovskite film is prepared without using an anti-solvent method:

[0139] 1. Mix FAI, PbI2, MACl, MAI, and CsI powders according to the molar ratio, add 1 mL of organic solvent (DMF:NMP=1000:192) to dissolve, and obtain Cs 0.05 FA 0.90 MA 0.05 PbI3 perovskite precursor solution; then adding SAM material to the perovskite precursor solution, wherein the amount of 2PACZ added is twice that of MeO-2PACZ (mass ratio of 2PACZ:MeO-2PACZ=2:1), and the concentration of 2PACZ in the perovskite precursor solution is 4 mg / mL;

[0140] 2. Clean the ITO glass and blow dry it with nitrogen;

[0141] 3. The perovskite precursor solution with added SAM material is used to prepare a perovskite film on ITO as a light absorption layer by a slit coating method. During the annealing process, the mixed SAM material in the perovskite precursor solution diffuses downward along the grain boundary of the perovskite, automatically assembles / buries at the bottom of the perovskite film to form a hole transport layer, and can passivate the defects of the perovskite film bulk and surface interface;

[0142] 4. Vacuum evaporation was performed on the perovskite film prepared in step 3 to deposit 30 nm thick C 60 , 6nm thick BCP and 150nm thick Au electrode.

[0143] Example 3

[0144] A perovskite solar cell 3 was prepared according to the method described in Example 2, wherein the difference between Example 3 and Example 2 is that:

[0145] The SAM materials added to the perovskite precursor solution are different. In Example 3, 2PACZ and Me-4PACZ are added, wherein the amount of Me-4PACZ added is the same as that of 2PACZ (mass ratio of 2PACZ:Me-4PACZ=1:1), and the concentration of 2PACZ in the perovskite precursor solution is 2 mg / mL;

[0146] Example 4

[0147] A perovskite solar cell 4 was prepared according to the method described in Example 2, wherein the difference between Example 4 and Example 2 is that:

[0148] The SAM materials added to the perovskite precursor solution are different. In Example 4, 2PACZ and DMAcPA are added, wherein the amount of DMAcPA added is twice that of 2PACZ (mass ratio of 2PACZ:DMAcPA=1:2), and the concentration of 2PACZ in the perovskite precursor solution is 2 mg / mL;

[0149] Example 5

[0150] A perovskite solar cell 5 was prepared according to the method described in Example 2, wherein the difference between Example 5 and Example 2 is that:

[0151] The SAM materials added to the perovskite precursor solution are different. In Example 5, DMAcPA and MeO-2PACZ are added, wherein the amount of DMAcPA added is twice that of MeO-2PACZ (the mass ratio of DMAcPA:MeO-2PACZ=2:1), and the concentration of DMAcPA in the perovskite precursor solution is 4 mg / mL;

[0152] Example 6

[0153] A perovskite solar cell 6 was prepared according to the method described in Example 2, wherein the difference between Example 6 and Example 2 is that:

[0154] The ratio of SAM materials added to the perovskite precursor solution was different from that in Example 2, wherein the amount of 2PACZ added was the same as that of MeO-2PACZ (mass ratio of 2PACZ:MeO-2PACZ=1:1), and the concentration of 2PACZ in the perovskite precursor solution was 4 mg / mL;

[0155] Example 7

[0156] A perovskite solar cell 7 was prepared according to the method described in Example 2, wherein the difference between Example 7 and Example 2 is that:

[0157] The mass ratio of 2PACZ and MeO-2PACZ added to the perovskite precursor solution was different from that in Example 2, wherein the mass ratio of 2PACZ:MeO-2PACZ=3:1, and the concentration of 2PACZ in the perovskite precursor solution was 3 mg / mL;

[0158] Example 8

[0159] A perovskite solar cell 8 was prepared according to the method described in Example 2, wherein the difference between Example 8 and Example 2 is that:

[0160] The mass ratio of 2PACZ and MeO-2PACZ added to the perovskite precursor solution was different from that in Example 2, wherein the mass ratio of 2PACZ:MeO-2PACZ=6:1, and the concentration of 2PACZ in the perovskite precursor solution was 3 mg / mL;

[0161] Example 9

[0162] A perovskite solar cell 9 was prepared according to the method described in Example 2, wherein the difference between Example 9 and Example 2 is that:

[0163] The mass ratio of 2PACZ and MeO-2PACZ added to the perovskite precursor solution was different from that in Example 1, wherein the mass ratio of 2PACZ:MeO-2PACZ=1:3, and the concentration of 2PACZ in the perovskite precursor solution was 2 mg / mL;

[0164] Example 10

[0165] A perovskite solar cell 10 is prepared according to the method described in Example 3, wherein the difference between Example 10 and Example 3 is that:

[0166] The mass ratio of Me-4PACZ and 2PACZ added to the perovskite precursor solution was different from that in Example 3, wherein the mass ratio of 2PACZ:Me-4PACZ=0.5:1, and the concentration of 2PACZ in the perovskite precursor solution was 2 mg / mL;

[0167] Embodiment 11

[0168] A perovskite solar cell 11 was prepared according to the method described in Example 3, wherein the difference between Example 11 and Example 3 is that:

[0169] The mass ratio of Me-4PACZ and 2PACZ added to the perovskite precursor solution was different from that in Example 3, wherein the mass ratio of 2PACZ:Me-4PACZ=1.5:1, and the concentration of 2PACZ in the perovskite precursor solution was 3 mg / mL;

[0170] Example 12

[0171] A perovskite solar cell 12 is prepared according to the method described in Example 3, wherein the difference between Example 12 and Example 3 is that:

[0172] The mass ratio of Me-4PACZ and 2PACZ added to the perovskite precursor solution was different from that in Example 3, wherein the mass ratio of 2PACZ:Me-4PACZ = 3:1, and the concentration of 2PACZ in the perovskite precursor solution was 3 mg / mL;

[0173] Example 13

[0174] A perovskite solar cell 13 is prepared according to the method described in Example 3, wherein the difference between Example 13 and Example 3 is that:

[0175] The mass ratio of Me-4PACZ and 2PACZ added to the perovskite precursor solution was different from that in Example 3, wherein the mass ratio of 2PACZ:Me-4PACZ=1:3, and the concentration of 2PACZ in the perovskite precursor solution was 2 mg / mL;

[0176] Embodiment 14

[0177] A perovskite solar cell 14 is prepared according to the method described in Example 4, wherein the difference between Example 14 and Example 4 is that:

[0178] The mass ratio of 2PACZ and DMAcPA added to the perovskite precursor solution was different from that in Example 4, wherein the mass ratio of 2PACZ:DMAcPA = 1:1, and the concentration of 2PACZ in the perovskite precursor solution was 3 mg / mL;

[0179] Embodiment 15

[0180] A perovskite solar cell 15 is prepared according to the method described in Example 4, wherein the difference between Example 15 and Example 4 is that:

[0181] The mass ratio of 2PACZ and DMAcPA added to the perovskite precursor solution was different from that in Example 4, wherein the mass ratio of 2PACZ:DMAcPA = 1:3, and the concentration of 2PACZ in the perovskite precursor solution was 1.5 mg / mL;

[0182] Example 16

[0183] A perovskite solar cell 16 was prepared according to the method described in Example 4, wherein the difference between Example 16 and Example 4 is that:

[0184] The mass ratio of 2PACZ and DMAcPA added to the perovskite precursor solution was different from that in Example 4, wherein the mass ratio of 2PACZ:DMAcPA = 1:5, and the concentration of 2PACZ in the perovskite precursor solution was 1 mg / mL;

[0185] Embodiment 17

[0186] A perovskite solar cell 17 was prepared according to the method described in Example 4, wherein the difference between Example 17 and Example 4 is that:

[0187] The mass ratio of 2PACZ and DMAcPA added to the perovskite precursor solution was different from that in Example 3, wherein the mass ratio of 2PACZ:DMAcPA = 3:2, and the concentration of 2PACZ in the perovskite precursor solution was 3 mg / mL;

[0188] Comparative Example 1

[0189] The perovskite solar cell 18 is prepared according to the method described in Example 2. The difference between Comparative Example 1 and Example 2 is that no SAM material is added to the perovskite precursor solution. The specific process is as follows:

[0190] 1. Mix FAI, PbI2, MACl, MAI, and CsI powders according to the molar ratio, add 1 mL of organic solvent (DMF: DMSO = 4:1) to dissolve, and obtain Cs 0.05 FA 0.90 MA 0.05 PbI3 perovskite precursor solution;

[0191] 2. Clean the ITO glass and blow dry it with nitrogen;

[0192] 3. Prepare a perovskite film as a light absorption layer on ITO by spin coating the perovskite precursor solution;

[0193] 4. On the perovskite film prepared in step 3 above, 30 nm thick C 60 , 6nm thick BCP and 150nm thick Au electrode.

[0194] Comparative Example 2

[0195] A perovskite solar cell 19 was prepared according to the method described in Example 1. The difference between Comparative Example 2 and Example 1 is that a SAM material (2PACZ) was added to the perovskite precursor solution. The specific process is as follows:

[0196] 1. Mix FAI, PbI2, MACl, MAI, and CsI powders according to the molar ratio, add 1 mL of organic solvent (DMF: DMSO = 4:1) to dissolve, and obtain Cs 0.05 FA 0.90 MA 0.05 PbI3 perovskite precursor solution; then adding SAM material to the perovskite precursor solution, wherein the final concentration of 2PACZ in the perovskite precursor solution is 6 mg / mL;

[0197] 2. Clean the ITO glass and blow dry it with nitrogen;

[0198] 3. The perovskite precursor solution with SAM material added is used to prepare a perovskite film as a light absorption layer on ITO by spin coating. During the process of adding anti-solvent and annealing, the SAM material in the perovskite precursor solution diffuses downward along the grain boundary of the perovskite, automatically assembles / buries at the bottom of the perovskite film to form a hole transport layer. At the same time, the SAM in the bulk and surface interface of the perovskite film can effectively passivate the defects of the perovskite film.

[0199] 4. Vacuum evaporation was performed on the perovskite film prepared in step 3 to deposit 30 nm thick C 60 , 6nm thick BCP and 150nm thick Au electrode.

[0200] Comparative Example 3

[0201] A perovskite solar cell 20 was prepared according to the method described in Example 2. The difference between Comparative Example 3 and Example 2 is that a SAM material (MeO-2PACZ) was added to the perovskite precursor solution, and the final concentration of MeO-2PACZ in the perovskite precursor solution was 6 mg / mL.

[0202] Comparative Example 4

[0203] A perovskite solar cell 21 was prepared according to the method described in Example 3. The difference between Comparative Example 4 and Example 3 is that the added SAM material is Me-4PACZ, and the final concentration of Me-4PACZ in the perovskite precursor solution is 3 mg / mL.

[0204] Comparative Example 5

[0205] The perovskite solar cell 22 was prepared according to the method described in Example 4. The difference between Comparative Example 5 and Example 4 is that the SAM material added was DMAcPA, and the final concentration of DMAcPA in the perovskite precursor solution was 3 mg / mL.

[0206] Comparative Example 6

[0207] A perovskite solar cell 23 was prepared according to the method described in Example 2, wherein the difference between Comparative Example 6 and Example 2 is that:

[0208] The perovskite precursor solution and the SAM material mixed solution are prepared separately. The specific process is as follows:

[0209] 1. Mix FAI, PbI2, MACl, MAI, and CsI powders according to the molar ratio, add 1 mL of organic solvent (DMF:NMP=1000:192) to dissolve, and obtain Cs 0.05 FA 0.90 MA 0.05PbI3 perovskite precursor solution; take the same mass of SAM materials Me-4PACZ and 2PACZ, add 1mL of isopropanol solution to dissolve, and the concentration of 2PACZ in the SAM material mixture is 2mg / mL;

[0210] 2. Clean the ITO glass and blow dry it with nitrogen;

[0211] 3. The SAM material mixture is spin-coated on the ITO to prepare a hole transport layer, and the solvent is removed by annealing (100° C., 10 min); then the perovskite precursor solution is spin-coated on the surface of the hole transport layer to prepare a perovskite film as a light absorption layer;

[0212] 4. Vacuum evaporation was performed on the perovskite film prepared in step 3 to deposit 30 nm thick C 60 , 6nm thick BCP and 150nm thick Au electrode.

[0213] The differences between Examples 1 to 17 and Comparative Examples 1 to 6 are shown in Table 1. The open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF) and photoelectric conversion efficiency (PCE) of the solar cells of Examples 1 to 17 and Comparative Examples 1 to 6 were tested respectively. The effective illumination area of ​​the cell is 0.07 cm 2 , the test results are shown in Table 2. The results of Examples 1 to 17 relative to Comparative Examples 1 to 5 show that, compared with not adding SAM material to the perovskite solution or adding only one SAM material, adding two SAM materials to the perovskite precursor solution can significantly improve the open circuit voltage, fill factor and photoelectric conversion efficiency of the perovskite solar cell. This is because the band gap of the mixed SAM and the band structure of the perovskite are more matched, thereby effectively reducing the open circuit voltage loss and significantly improving the transmission and extraction efficiency of holes. Secondly, the addition of multiple SAM materials can effectively passivate various defects of the perovskite film, reduce the non-radiative recombination of carriers, and ultimately improve the efficiency of the battery.

[0214] The results of Examples 1 to 17 relative to Comparative Example 6 show that compared with the step-by-step preparation of the hole transport layer and the perovskite absorption layer, the hole transport layer and the perovskite absorption layer prepared in one step by the present application have better short-circuit current and fill factor, and the final perovskite solar cell prepared has a higher photoelectric conversion efficiency. This may be because after the hole transport layer is prepared separately, due to the poor wettability of the SAM surface, the quality of the perovskite film prepared on the SAM surface is poor, resulting in a high battery leakage current and more internal defects in the perovskite film, thereby reducing the photoelectric conversion efficiency of the battery. The perovskite film prepared by the self-buried bottom method has better crystallization quality and lower internal defect density of the film, so the photoelectric conversion efficiency of the battery is significantly improved.

[0215] Table 1

[0216]

[0217]

[0218]

[0219] Table 2

[0220] Voc(V) FF(%) <![CDATA[Jsc(mA / cm 2 )]]> PCE(%) Example 1 1.19 85.11 23.01 23.29 Example 2 1.18 85.33 23.22 23.48 Example 3 1.18 83.94 23.57 23.42 Example 4 1.17 83.36 23.50 22.97 Example 5 1.18 84.47 23.26 23.14 Example 6 1.17 85.38 22.74 22.76 Example 7 1.18 84.91 22.78 22.73 Example 8 1.17 80.28 22.81 21.36 Example 9 1.17 81.92 22.74 21.77 Example 10 1.16 84.01 23.39 22.84 Embodiment 11 1.17 85.29 23.29 23.23 Example 12 1.17 85.34 23.12 22.99 Embodiment 13 1.16 84.48 23.26 22.84 Embodiment 14 1.17 81.75 23.19 22.14 Embodiment 15 1.17 82.28 23.01 22.10 Example 16 1.17 81.30 22.59 21.54 Embodiment 17 1.17 79.73 23.47 21.81 Comparative Example 1 0.79 42.89 22.55 7.63 Comparative Example 2 1.14 79.22 22.75 20.62 Comparative Example 3 1.13 78.74 22.78 20.27 Comparative Example 4 1.15 76.68 22.33 19.75 Comparative Example 5 1.15 76.13 22.47 19.63 Comparative Example 6 1.17 78.64 22.49 20.72

[0221] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0222] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing a hole transport layer, characterized in that: include: applying the solution on a substrate and performing an annealing treatment to form a hole transport layer; Wherein, the solution includes a perovskite precursor and at least two self-assembled monomolecular materials.

2. The method according to claim 1, characterized in that There are two types of self-assembled monomolecular materials, and the mass ratio of the two types of self-assembled monomolecular layer materials is 1:1 to 1:

10.

3. The method according to claim 1 or 2, characterized in that: The self-assembled monomolecular material includes at least one of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid, (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanotitanyl)phosphonic acid and [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid.

4. The method according to claim 2, characterized in that: The two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid; And / or, the two self-assembled monomolecular materials include [2-(9H-carbazole-9-yl)ethyl]phosphonic acid and [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid; And / or, the two self-assembled monomolecular materials include [2-(9H-carbazol-9-yl)ethyl]phosphonic acid and [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid; And / or, the two self-assembled monomolecular materials include [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazol-9-yl)ethyl]phosphonic acid.

5. The method according to claim 4, characterized in that The mass ratio of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid is (1-3):1; and / or, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to the [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid is (0.5-1.5):1; and / or, the mass ratio of the [2-(9H-carbazole-9-yl)ethyl]phosphonic acid to the [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid is 1:(1-3); And / or, the mass ratio of [4-(2,7-dibromo-9,9-dimethylacridin-10(9H)yl)butyl]phosphonic acid and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid is (1-3):

1.

6. The method according to claim 1, characterized in that The concentrations of the at least two self-assembled monomolecular materials in the solution are respectively 0.5 mg / mL to 20 mg / mL.

7. The method according to claim 6, characterized in that The concentrations of the at least two self-assembled monomolecular materials in the solution are 1 mg / mL to 10 mg / mL respectively.

8. The method according to claim 1, characterized in that The annealing process includes one-step annealing or two-step annealing.

9. The method according to claim 8, characterized in that The one-step annealing is carried out at 60-180° C. for 1-80 min; And / or, the two-step annealing includes firstly performing annealing at 50-100° C. for 1-30 min; and then performing annealing at 80-180° C. for 1-60 min.

10. The method according to claim 1, characterized in that The perovskite precursor is provided in the form of a perovskite precursor solution.

11. The method according to claim 10, characterized in that The perovskite precursor solution is prepared by the following method: The metal halide, the organic salt halide and the organic solvent are mixed to obtain a perovskite precursor solution.

12. A hole transport layer, characterized in that: The method is prepared by any one of claims 1 to 11.

13. A hole transport layer, characterized in that: include: It is composed of at least two self-assembled monomolecular materials; The self-assembled monomolecular material includes [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid, (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanotitanyl)phosphonic acid or [4-(2,7-dibromo-9,9-dimethylacridine-10(9H)yl)butyl]phosphonic acid.

14. A perovskite solar cell, characterized in that: include: substrate; A hole transport layer, the hole transport layer is as defined in any one of claims 12 to 13, and the hole transport layer is disposed on one side of the substrate; A perovskite absorption layer, wherein the perovskite absorption layer is arranged on a side of the hole transport layer away from the substrate; An electron transport layer, wherein the electron transport layer is arranged on a side of the perovskite absorption layer away from the hole transport layer; An electrode layer is disposed on a side of the electron transport layer away from the perovskite absorption layer.

15. A perovskite tandem battery, comprising: A top cell and a bottom cell, wherein the top cell is the perovskite solar cell according to claim 14, and the top cell is arranged on the upper surface of the bottom cell.

16. An electrical equipment, characterized in that: include: The perovskite solar cell according to claim 14 or the perovskite tandem cell according to claim 15.

Citation Information

Cited By

  • Anti-solvent-resistant trans-perovskite solar cell and preparation method thereof

    CN119630253A

  • Perovskite thin film manufacturing method and apparatus, and perovskite solar cell module

    WO2026170610A1